Use of infrared thermography in early detection of Phlebitis in adult patients with Peripheral Intravenous Catheters (I-TEPID): study protocol for an observational study - Daud, Azlina; Tang, Li Yoong; Corley, Amanda; Marsh, Nicole; Hashim, Nur Hafiza; Mohd Mokhtar, Hanida Hani; Nik Mohd Hatta, Nik Noor Kaussar; Jaafar, Siti Nur Illiani; Mat Isa, Rif'Atunnailah (Universiti Putra Malaysia, 2025)
Introduction: The ability of Infrared thermography (IFT) to provide accurate detection of phlebitis is unknown due to external factors that may potentially influence temperature measurement and lead to misdiagnosis of phlebitis. Furthermore, its applicability and effectiveness as a diagnostic tool needs further testing. This study aims to examine peripheral intravenous catheter (PIVC) insertion site temperatures, body temperature distal and proximal to the insertion site, Visual Infusion Phlebitis (VIP) score and its associated factors that subsequently contribute to IFT as a diagnostic tool to detect the early manifestation of phlebitis. Methods: This study is a cohort study with convenience sampling in patients admitted to medical, surgical, and orthopedic wards. Inclusion criteria include adults aged ≥18, on day one of PIVC insertion, and expected to retain the PIVC for at least three days. Patients with laboratory-confirmed positive blood cultures within 24 hours of screening, known allergy to study products, current or high-risk of skin tear. 388 patients will be recruited, and all eligible participants will be invited to participate after providing written informed consent. Assessment of body temperature, VIP score and PIVC site temperature will be carried out daily starting on day 1 of PIVC insertion until day 5 of PIVC insertion. The association between PIVC insertion site temperature and VIP score of phlebitis from day 1 to day 5 will be analysed using One-Way ANOVA. Discussion: The use of IFT may allow early detection of phlebitis and reduce nursing workload associated with the assessment of patients with PIVCs, thereby substantially reducing healthcare costs and improving patient satisfaction and outcomes. Trial Registration: Ethical approval is granted by the International Islamic University Malaysia Research Ethic Committee (IIUM/504/14/11/2/IREC2022-KON).